Gingival health status of primary school children in a Nigerian community - O, Osadolor O (Update Dental College Journal, 2021)
Background: Gingival status is a part of periodontal health. Periodontal health may be defined as absence of gingivitis, periodontitis or other periodontal conditions. Objective: To assess the gingival health status of 11 year old primary school children in a rural community in south -east Nigeria Methodology: A cross sectional descriptive study of 11 year old primary school children was done in a public primary school in Nkanu -West local Government Area of Enugu State. Ethical clearance for this study was sought and obtained. Socio-demographic data was obtained using interviewer-administered questionnaire. Gingival examination was done by a single examiner (k= 0.76), intra examiner calibration (five children per session) was done prior to data collection, The gingival status was assessed according to the gingival index of Loe and Silness. Statistical analysis was done using SPSS Version 20. P values < 0.05 were accepted as being statistically significant Results: 22 (46.3%) females, 28(53.7%) males were seen and examined, giving a female to male ratio of about 1:1.3. 2(4 %) had healthy gingiva, 47(94 %) had mild gingivitis , 1(2 %) had moderate gingivitis and none of the participants had severe gingivitis. Mild gingivitis were seen more in males than females. Majority of the school children duration of tooth brushing was about two minutes. Conclusion: Gingival status is a part of periodontal health. In this study, gingivitis were seen more in males than females, only marginal gingivitis were seen among the school children and none had severe gingivitis. Update Dent. Coll. j: 2021; 11 (1): 16-19